Māori in Engineering Podcast, Episode 9: Georgina Stokes: designing how we experience and understand spaces - Stokes G; Lysaght A (Māori in Engineering Podcast, 2022)
Episode 19 of The Māori in Engineering podcast is now live! A long time coming in getting episodes out, mō taku hē. So it was great to dust off the mic! Awesome to catch up with Georgina Stokes (Ngāi Tahu) - someone who is an incredible thinker in the spatial design space and inspiration to those she lectures at Toi Rauwhārangi College of Creative Arts at Massey University kei Te Whanganui a Tara. Georgina is an overall awesome wahine, pretty evident in the way she communicates so passionately with the work. Really interesting points of discussions was her mahi in whakapapa plotting to better how we experience spaces and the alignment in her studies and her Māoritanga 🤯 Available on all podcast platforms and the website https://lnkd.in/gPkURGxB Listen on Spotify here: https://lnkd.in/gz3xkQyj #MāoriinEngineering
Keywords: Mātauranga Māori; Whakapapa; Spatial Design